Pemberdayaan Masyarakat Rusunawa Tambaan melalui Pelatihan Inovasi dan Diversifikasi Produk Olahan Ikan Lele Bernilai Tambah - Arifianto, Endra Yuafanedi; Saleh, Akhmad Muwafik; Anandya, Asyifa; Hafidzi, Rana Aliyya; Angestiana, Lu’lu Nadia; Silfiani, Firli Tri; Mukarromah, Rani Cahyatul (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The high national production of catfish has not been accompanied by sufficient diversification of value-added processed products, creating an urgent need for innovation at the community level. This community service program aimed to enhance the skills of residents of Rusunawa Tambaan specifically members of the Pokdakan Benih Unggul Rusunawa in producing innovative catfish-based products. The program employed a participatory approach consisting of three stages: preparation (needs assessment and training module development), implementation (socialization, demonstrations, and hands-on practice), and evaluation (pretest, posttest, observations, and interviews). The activity was conducted on 18 September 2025 and involved 20 participants from the local catfish farming group. Training materials included the production of frozen seasoned catfish in four flavor variants, smoked catfish, and catfish nuggets. Evaluation results indicated an average increase of 55% in participants’ knowledge scores after training, demonstrating successful skill transfer. High levels of enthusiasm, active engagement, and two-way interaction further supported the effectiveness of the participatory method. The program also offers novelty by integrating three types of processed products with multiple flavor variations within a single training session. Overall, the training strengthened community capacity to develop value-added catfish products and provided a practical foundation for enhancing the economic resilience of fishery-based households in urban settings.ABSTRAKProduksi ikan lele nasional yang tinggi belum diimbangi keberagaman produk olahan bernilai tambah, sehingga diperlukan inovasi untuk meningkatkan pemanfaatannya. Kegiatan pengabdian masyarakat di Rusunawa Tambaan ini bertujuan meningkatkan keterampilan anggota Pokdakan Benih Unggul Rusunawa dalam mengolah ikan lele menjadi produk inovatif. Pelaksanaan kegiatan menggunakan pendekatan partisipatif melalui tiga tahapan, yaitu persiapan (survei kebutuhan dan penyusunan modul), pelaksanaan (sosialisasi, demonstrasi, dan praktik langsung), serta evaluasi (pretest, posttest, observasi, dan wawancara). Kegiatan berlangsung pada 18 September 2025 dan melibatkan 20 peserta dari kelompok budidaya lele setempat. Materi pelatihan mencakup pembuatan lele bumbu beku dengan empat varian rasa, lele asap, dan nugget lele. Hasil evaluasi menunjukkan peningkatan skor pengetahuan peserta sebesar rata-rata 55% setelah mengikuti pelatihan, mengindikasikan keberhasilan transfer keterampilan. Antusiasme peserta, interaksi dua arah, serta keterlibatan aktif dalam praktik menunjukkan bahwa pendekatan partisipatif efektif meningkatkan kapasitas masyarakat. Kegiatan ini memiliki unsur kebaruan karena mengintegrasikan tiga jenis produk dan beberapa varian rasa dalam satu rangkaian pelatihan. Pelatihan diversifikasi produk olahan lele memberikan kontribusi nyata terhadap peningkatan keterampilan pengolahan pangan serta membuka peluang penguatan ekonomi masyarakat berbasis usaha perikanan di kawasan perkotaan.